Treatment of neoplastic pleural effusion with iodinated talc - Vasallo, Bartolomé; Caruso, Enrique (Cirugía del Uruguay, 1982)
Our experience with iodized tale poudrage for controlling recurrent malignant pleural effusions in presented. The method was perfomed in 23 patients; 16 of the patients were benefited by control of their effusion, full lung expansion and dissappearance of the dyspnea. In 4 patients with good control of their effussion and dissapearance of the dyspnea the lung expansion was incomplete. Three patients didn't improve following poudrage. Nineteen patients have died for their primary cancer disease. The survival time of these patients ranged from 1 to 36 month, with an averag of 7,7 months. Four patients lived more than a year. (14, 24, 27 and 36 months). We believe that iodized tale poudrage is a usefull palliative procedure in selected group of patients with recurrent malignant pleural effusion, satisfactory general condition and logical life expectancy.